The asymmetric relationship between smoking and sleep: Longitudinal findings from Dutch panel data - Brian M. Doornenbal (European Publishing, 2021)
Introduction Smokers typically experience more sleep problems than non-smokers, so sleep problems are frequently reported by smokers who are attempting to quit and these can be expected to develop also after initiation of smoking. However, little is known about the effects of starting smoking on sleep problems. Some research suggests smoking reduces stress, which indicates that some aspects of smoking could benefit sleep. This study aims to contribute to the understanding of the asymmetry of the relationship between smoking and sleep problems.